miR-193a-3p prevents tumour progression by targeting TCL1 in diffuse large B-cell lymphoma - Haixia Gao; Mengbo Wang; Shuchen Xiong; Ran Zhang; Cancan Wang; Huan Zhang; Wenli Ji; Cuicui Wang; Zhiying Jia; Xinxia Li (Journal of Translational Medicine)
Abstract Both miR-193a-3p and T-Cell Leukemia/Lymphoma 1 (TCL1) are enriched in the PI3K/AKT signaling pathway, which is pivotal for the regulation of the initiation and progression of diffuse large B-cell lymphoma (DLBCL). Although miR-193a-3p has been demonstrated to exert an inhibitory effect in various tumors, the relationship between miR-193a-3p and TCL1, as well as the mechanisms by which miR-193a-3p participates in the modulation of DLBCL onset and progression, remain to be elucidated. The expression levels of miR-193a-3p and TCL1 in DLBCL cells were examined using quantitative real-time polymerase chain reaction (qRT-PCR), and their impact on DLBCL cell growth was assessed through cell proliferation assays and flow cytometry. Subsequently, the interaction between miR-193a-3p and TCL1 was investigated using a dual-luciferase reporter assay. A nude mouse model of subcutaneous DLBCL was established in which the mice were injected with miR-193a-3p agomir, and were evaluated after 45 days. Finally, the mechanism by which miR-193a-3p modulates the PI3K/AKT signaling pathway was explored via qRT-PCR and Western blotting analyses. It was found that miR-193a-3p is downregulated, while TCL1 is upregulated in DLBCL. miR-193a-3p was shown to inhibit proliferation and induce apoptosis in DLBCL cells, in contrast to TCL1, which promotes proliferation and suppresses apoptosis. Moreover, TCL1 was identified as a target gene of miR-193a-3p. Additionally, it was demonstrated that miR-193a-3p regulates the PI3K/AKT signaling pathway through TCL1 both in vitro and in vivo. Collectively, these findings indicate that miR-193a-3p suppresses the growth of DLBCL by targeting TCL1 within the PI3K/AKT signaling pathway.